The Position of the Licensee Regarding Violations of Related Rights (Broadcasting Rights) in the Perspective of Unlawful Acts : Case Study of Case Number 12/PDT.SUS-HKI/CIPTA/2018/ PN.NIAGA.Sby) - Zain Sumawang, Hanisa; Roisah, Kholis (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines dispute number 12/PDT.SUS-HKI/CIPTA/2018/PN.NIAGA.Sby involving violations of broadcasting rights. Moral and economic rights in the context of Copyright are in focus. The research uses normative juridical methods with a statutory approach. The results include a detailed analysis of violations by PT. Widhi Hartajaya (Suris Boutique Hotel) and the Supreme Court decision which sentenced him to pay material compensation. In the discussion, the research links the findings to copyright theory and related literature. The conclusion confirms copyright infringement, reminding us of the urgency of exclusive protection and law enforcement. Recommendations include interdisciplinary dimensions, comparative studies, and technological exploration in managing Copyright. The research is expected to contribute to understanding law enforcement and copyright protection in Indonesia.